The research progress of interventions of exudate from abdominal drainage tube (腹腔引流管管口渗液应对方法的研究进展) - LIU Min (刘敏) (中西医结合护理)
This paper summarized the interventions dealing with exudate from abdominal drainage tube. Methods aiming to reduce the exudate were listed as follows: placement of drainage tube with extraperitoneal tunnel method, choice of reasonable pipeline, reducing the causes of elevated intra-abdominal pressure, maintaining drainage tube patency. Disposed methods after occurrence of exudate were as follows: application of foam dressings, hydrocolloid dressings, fixed tubes, usage of a pocket to collect exudates and building an integrated model for prevention of exudate. This paper also aimed to provide reference for nursing workers to prevent and deal with exudate from abdominal drainage tube, improve patient comfort, reduce medical workload and improve nursing quality. (本文总结了腹腔引流管管口渗液的应对方法, 包括减少渗液的方法(采用腹膜外隧道法放置引流管、合理选择管道、减少引起腹内压增高的相关因素、保持腹腔引流管通畅)及出现渗液后的处理方法(包括使用泡沫敷料、使用水胶体敷料固定导管、使用造口袋收集渗液、构建整合医学模式处理渗液问题), 为护理工作者预防和处理引流管管口渗液提供参考, 提高患者舒适度, 减少医疗工作量, 提高护理质量。)